2006
DOI: 10.1159/000094779
|View full text |Cite
|
Sign up to set email alerts
|

Proteomic Analysis of Serum, Outflow Dialysate and Adsorbed Protein onto Dialysis Membranes (Polysulfone and PMMA) during Hemodialysis Treatment Using SELDI-TOF-MS

Abstract: Aims: Alterations in the profiling of peptides and proteins in the serum, outflow dialysate and adsorbed protein on the dialysis membrane were investigated. Methods: Alterations in the protein profiling of routine hemodialysis using polysulfone (TS-UL) and PMMA (moderate flux membrane of polymethylmethacrylate: BK-U) in 8 patients and that of adsorption onto polysulfone and PMMA membranes in 4 patients were evaluated by SELDI-TOF-MS and ProteinChip array. Mass-to-charge ratios (m/z) between 2,000 and 120,000 w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
29
0
1

Year Published

2007
2007
2016
2016

Publication Types

Select...
7
2

Relationship

0
9

Authors

Journals

citations
Cited by 41 publications
(30 citation statements)
references
References 33 publications
0
29
0
1
Order By: Relevance
“…[31][32][33][34][35] or clusterin (spot nos. [23][24][25]. The protein identifications were further verified by the comparison of measured pI and MW (estimated by the coordinates of the spots in gel) with their theoretical values (as predicted by the protein database).…”
Section: Resultsmentioning
confidence: 99%
“…[31][32][33][34][35] or clusterin (spot nos. [23][24][25]. The protein identifications were further verified by the comparison of measured pI and MW (estimated by the coordinates of the spots in gel) with their theoretical values (as predicted by the protein database).…”
Section: Resultsmentioning
confidence: 99%
“…These peaks were putatively identified as representing B2M. 18,19 Other peaks found to be higher in the PAD group were 13-and 15-kDa proteins putatively identified as cystatin C and lysozyme C, respectively. Furthermore, unidentified proteins at 22 and 36 kDa were increased in the PAD group.…”
Section: High-throughput Proteomics Analysismentioning
confidence: 94%
“…A subsequent investigation revealed that the β 2 -MG level in the dialysate was extremely low when a PMMA dialyzer (BK Series®) was used for hemodialysis and that this phenomenon was due to adsorption of β 2 -MG to PMMA membrane [27]. Another subsequent investigation demonstrated that β 2 -MG was detectable in the filtrate after the adsorption capacity of the PMMA dialyzer reached saturation level over time [28].…”
Section: Pmma Hemofiltermentioning
confidence: 97%